An insight into the theoretical investigation of possible piezoelectric effect in samarium titanate (SmTiO3) - Costa, E. B.; Farias, M. S.; de Miranda, R. M.; dos Santos, M. A. B.; Lobato, M. S.; de Figueiredo, A. F.; Ferreira, R. D. P.; Gil, F. S.; Pinheiro, J. C.; Treu-Filho, O. [UNESP]; Kondo, R. T. (Elsevier B.V., 2009)
The perovskite structure is the most important piezoelectric crystalline structure. In this paper, the Douglas-Kroll-Hess second-order scalar relativistic method is applied for investigation of the possible piezoelectricity in the samarium titanate (SmTiO3). Initially, to aim at an adequate representation of the many-electron environment of SmTiO3 through a very good description of the total and the orbital energies (epsilon(HOMO) and epsilon(HOMO)-1) of the system's constituent fragments, the generator coordinate HF (GCHF) method was applied to build Gaussian basis sets, which were contracted to (25s16p)/[5s4p] for the O (P-3) atom, to (29s18p12d)/[9s5p3d] for the Ti (S-5) atom, and to (32s22p16d10f)/[16s11p7d3f] for Sm (F-7) atom and after supplementation with polarization and diffuse functions, they were used to investigate the property of interest in the considered system. The calculations and the analysis of total energy, dipole moment and atomic charges evidence that the possible piezoelectric effect in the SmTiO3 is caused by electrostatic interactions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Samarium titanate; Possible piezoelectric effect; Theoretical investigation; Gaussian basis sets; GCHF method